2021
DOI: 10.1371/journal.pone.0246194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a tart cherry (Prunus cerasus L.) phenolic extract on Porphyromonas gingivalis and its ability to impair the oral epithelial barrier

Abstract: Periodontal diseases, including gingivitis and periodontitis, are a global oral health problem. Porphyromonas gingivalis, a key pathogen involved in the onset of periodontitis, is able to colonize the subgingival epithelium and invade the underlying connective tissue due to the contribution of cysteine proteases known as gingipains. In this study, we investigated the effects of a phenolic extract prepared from tart cherry (Prunus cerasus L.) juice on the growth, adherence, and protease activity of P. gingivali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The relative position of the hydroxyl group in the phenolic compounds and the types of alkyl substituents incorporated into the non-phenolic ring structure could also affect the antibacterial activity (Dorman and Deans, 2000). In our study, the YAP showed a certain antibacterial activity, but the antibacterial activity was lower than other natural phenolic extracts, such as tea polyphenols and tart cherry phenolic extract (Lagha et al, 2017(Lagha et al, , 2021. In order to improve the antibacterial activity of YAP, the structure of YAP should be further studied and modified in the future.…”
Section: Discussionmentioning
confidence: 61%
“…The relative position of the hydroxyl group in the phenolic compounds and the types of alkyl substituents incorporated into the non-phenolic ring structure could also affect the antibacterial activity (Dorman and Deans, 2000). In our study, the YAP showed a certain antibacterial activity, but the antibacterial activity was lower than other natural phenolic extracts, such as tea polyphenols and tart cherry phenolic extract (Lagha et al, 2017(Lagha et al, , 2021. In order to improve the antibacterial activity of YAP, the structure of YAP should be further studied and modified in the future.…”
Section: Discussionmentioning
confidence: 61%
“…The extract also exerted a protective effect on the integrity of the oral epithelial barrier in an in vitro model infected with P. gingivalis. Furthermore, it prevented a decrease in trans-epithelial electrical resistance as well as the destruction of tight junction proteins (zonula occludens-1 and occludin) (55) .…”
Section: Prunus Cerasusmentioning
confidence: 99%